AB0374 LUPUS LOW DISEASE ACTIVITY STATE AND MAINTAINING DRUG THERAPY: A RETROSPECTIVE INVESTIGATION. (2nd June 2020) - Gotelli, E.; Sulli, A.; Ferrari, G.; Pacini, G.; Schenone, C.; Patanè, M.; Bica, P. F.; Pizzorni, C.; Cutolo, M.; Paolino, S.
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune multisystemic disease, that can begin with a wide range of clinical manifestations, and requires immunosuppressive therapies (1). A treat-to-target strategy leads to a high rate of clinical remission among patients (2). Several "remission" definitions have been provided in the last years and Lupus Low Disease Activity State (LLDAS) seems one of the best tools to evaluate it in clinical practice (3). Objectives: To evaluate the prevalence of SLE signs and symptoms at onset and the drugs used to induce and maintain the clinical remission, evaluated by LLDAS, in a real-life cohort of SLE patients. Methods: Thirty female SLE patients (mean age 52±15 years; mean age at disease onset 34±16 years, mean disease duration 18±13 years) in clinical remission have been enrolled (EULAR/ACR 2019 criteria) (4). Remission was defined by LLDAS (SLEDAI-2K < 4 and no activity in major organ systems, no hemolytic anemia; no new features of activity compared with previous assessment, physician global assessment (PGA) ≤ 1, prednisone dose ≤7.5 mg/day, well tolerated and stable therapy with maintenance doses of immunosuppressive drugs). Clinical and serological manifestations, SLEDAI-2K and pharmacological treatments were recorded at baseline and during follow-up. Results: Mucocutaneous involvement (57%), arthritis (30%), serositis (30%), nephritis (27%), leukopenia (23%), thrombocytopenia (20%), hemolytic anemia (13%), antiphospholipid syndrome manifestations (16%), neuro-psychiatric lupus symptoms (6%) were present in various combinations at disease onset. Baseline mean SLEDAI-2K was 10.5±2.5. Patients were treated with different dosages of glucocorticoids (100%), hydroxychloroquine (HCQ, 73%), cyclofosfamide (20%), mycophenolate mofetile (MMF, 13%), azathioprine (AZA, 13%), methotrexate (MTX, 13%), cyclosporine A (CSA, 6%), rituximab (3%), abatacept (ABA, 3%). Glucocorticoids were prescribed together with a single DMARD in 50% of cases and with two DMARDs in the remaining 50% of patients. Patients reached LLDAS remission after a mean time of 14±12 years, with a mean remission duration of 4.2±3.2 years (mean SLEDAI-2K at last visit 1±1; Mean PGA 0.4±0.1). Maintenance therapies during remission were prednisone ≤ 5 mg/day and/or HCQ ≤ 400 mg/day and/or CSA ≤ 200 mg/day and/or MTX ≤ 10 mg/weekly and/or MMF ≤ 2 g/day and/or AZA ≤ 100 mg/day. In particular, only prednisone 7%, only HCQ 3%, prednisone + HCQ 53%, prednisone + single DMARD (different from HCQ) 7%, prednisone + HCQ + DMARDs 30%. Conclusion: After reaching the clinical remission by a treat to target strategy, the administration of low dose of prednisone and HCQ in the majority of SLE patients (63%) seems useful to prevent new SLE flares. The retrospective design and the absence of a control group of patients with active disease limit this study. References: [1 ]Lisnevskaia L et al. 2014. Lancet 384(9957):1878-1888. [2 ]Van Vollenhoven RF et al. 2014. Ann Rheum Dis 73(6): 958-967. [3 ]Franklyn K et al. 2016. Ann Rheum Dis . 75(9): 1615-21. [4 ]Aringer M et al. 2019. Arthritis Rheumatol. 71(9): 1400-1412. Disclosure of Interests: Emanuele Gotelli: None declared, Alberto Sulli Grant/research support from: Laboratori Baldacci, Giorgia Ferrari: None declared, Greta Pacini: None declared, Carlotta Schenone: None declared, Massimo Patanè: None declared, Pietro Francesco Bica: None declared, Carmen Pizzorni: None declared, Maurizio Cutolo Grant/research support from: Bristol-Myers Squibb, Actelion, Celgene, Consultant of: Bristol-Myers Squibb, Speakers bureau: Sigma-Alpha, Sabrina Paolino: None declared